Neutron measurement at the thermal column of the Malaysian Triga Mark II reactor using gold foil activation method and TLD - Shalbi S.; Wan Salleh W.N.; Idris F.M.; Ashraff Rosdi M.A.; Sarkawi M.S.; Jamsari N.L.; Mohd Nasir N.A. (Institute of Physics Publishing, 2023)
Chemical activation; Facilities; Gold; Neutron detectors; Neutron flux; Neutrons; Nuclear reactors; Reactor cores; Shielding; Activation method; Boron neutron capture therapy; Design facilities; Epithermal neutron; Feasibility studies; Flux measurements; Neutron measurements; Thermal neutrons; Reactor shielding